West Sumatra Brown Rice resistance to Brown Planthopper and Blast Disease - INDRA DWIPA; AUZAR SYARIF; IRFAN SULIANSYAH; ETTI SWASTI (Society for Indonesian Biodiversity, 2018)
Dwipa I, Syarif A, Suliansyah I, Swasti E. 2018. West Sumatra Brown Rice resistance to Brown Planthopper and Blast Disease. Biodiversitas 19: 893-898. Brown rice is a highly nutritious rice widely consumed as the carbohydrate substitute of common rice. Brown rice resistance to biotic stress is one of indicators of a superior variety. Our study aimed to analyze the response of several brown rice genotypes from West Sumatra to brown planthopper attack and blast disease. This study comprised two experiments, the resistance assay to brown planthopper (Nilaparvata lugens (Stal.) and the resistance assay to blast fungi Pyricularia oryzae. The resistance assay to brown planthopper was done using randomized block design experiment with three replicates. Eighteen brown rice genotypes (15 brown rice, 2 black rice, and 1 control genotype) were tested in the assay. From 17 brown and black rice tested, 7 genotypes were resistant and 2 were moderately resistant. For blast resistance analysis, fifteen rice genotypes (13 brown rice and 2 black rice) were used. There was only 1 genotype highly resistant and 3 moderately resistant to blast disease among those 15 brown and black rice.